Modelling, optimisation and performance evaluation of a parabolic trough solar collector steam generation system - Lloyd, Stephen J.; Ward, John Paul; Kalogirou, Soteris A.; Lloyd, Stephen J.; Ward, John Paul (My University, 1997)
A parabolic trough collector (PTC) system used for steam generation is presented in this paper. PTCs are the preferred type of collectors used for steam generation due to their ability to work at high temperatures with a good efficiency. The modelling program developed called PTCDES is used to predict the quantity of steam produced by the system. The flash vessel size, capacity and inventory determines how much energy is used at the beginning of the day for raising the temperature of the circulating water to saturation temperature before effective steam production begins. Optimisation of the flash vessel presented here uses a simplified version of the program PTCDES. System performance tests indicate that the modelling program is accurate to within 1.2% which is considered very adequate. Finally, the theoretical system energy analysis is presented in the form of a Sankey diagram. The analysis shows that only 48.9% of the available solar radiation is used for steam generation. The rest is lost either as collector or thermal losses.
Keywords: Steam generation; System energy analysis